Вплив гамма-опромінення на ознаки продуктивності м’якої пшениці в залежності від генотипу і умов вирощування - Созінов, І.О.; Козуб, Н.О.; Бідник, Г.Я.; Дем'янова, Н.О.; Карелов, А.В.; Блюм, Я.Б.; Созінов, О.О. (Фактори експериментальної еволюції організмів, 2014)
Aims. The effect of gamma-irradiation on productivity of common wheat plants differing in the dose of the 1BL/1RS translocation under different growth conditions was studied. Methods. Dry F₂ seeds from crossing Bezostaya 1 lines were treated with gamma-radiation at 150, 200, and 300 Gy and grown in two localities. Each F₂ plant was characterized with respect to yield traits. The presence of the translocation was analyzed by electrophoresis of gliadins. Results. Under unfavorable conditions the LD50 dose was close to 200 Gy, whereas under favorable ones it was 300 Gy. In variants with irradiation under unfavorable conditions homozygotes for the rye translocation showed the least decrease in the main productivity traits, the highest decrease was observed in homozygotes without it. Conclusions. The results suggest lower sensitivity of genotypes with the 1BL/1RS translocation to stress factors (high-dose gamma-irradiation of dry seeds) in comparison with genotypes without it.

Key words: Triticum aestivum L., 1BL/1RS translocation, gamma-irradiation, productivity.